2016
DOI: 10.1080/02640414.2016.1265660
|View full text |Cite
|
Sign up to set email alerts
|

The effect of unilateral balance training on postural control of the contralateral limb

Abstract: To investigate the impact of unilateral balance training on postural control of the trained and contralateral limb in healthy elderly. Fifty-one healthy old adults were randomly assigned into training group (TG) and control group (CG). Participants of the TG performed unilateral balance training (dominant (DOM) leg) over 4 weeks (4×/week). Centre of pressure analysis was performed at baseline, 5 weeks follow-up and 9 weeks follow-up under the following conditions: (1) one-leg stance without additional task, (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(50 citation statements)
references
References 36 publications
2
47
0
1
Order By: Relevance
“…In the case of asymmetric pathologies (e.g., hemiplegia), results of the affected limb can be compared with the healthy one [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of asymmetric pathologies (e.g., hemiplegia), results of the affected limb can be compared with the healthy one [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…All the studies carried out on the basis of balance training (in various postural conditions: static, dynamic, unstable, progressive postural difficulty, with or without sensory manipulation) show that ipsilateral and/or contralateral monopedal postural control was improved after periods of 3-5 sessions weekly for 4-8 weeks (Rasool and George, 2007;Oliveira et al, 2013;Hale et al, 2014;El-Gohary et al, 2016;Schlenstedt et al, 2017). By contrast, the effects of resistance training of the ipsilateral limb on the contralateral monopedal postural control are much less clear since Kim et al (2011) reported that contralateral monopedal postural control was improved after 4 sessions weekly for 2 weeks while Kadri et al (2017) concluded that contralateral monopedal postural control was not improved after 3 sessions weekly for 8 weeks with either voluntary contractions or electro-induced contractions.…”
Section: Cross-education and Postural Control: Effects Of Training Avmentioning
confidence: 99%
“…Improvement in monopedal postural control of the contralateral limb after balance training can be ascribed to neural adaptations (Rasool and George, 2007;Oliveira et al, 2013;Hale et al, 2014;El-Gohary et al, 2016;Schlenstedt et al, 2017). The studies that have evaluated the effects of resistance training are not as clear and unanimous (Kim et al, 2011;Kadri et al, 2017).…”
Section: Mechanistic Explanations Suggestedmentioning
confidence: 99%
See 1 more Smart Citation
“…Schlenstedt et al 15) reported that the distance of the COP shift in the front-back direction decreased significantly after single-leg balance exercise. Therefore, we can expect that single-leg reach balance training will improve the toe grip strength and stabilize the COP position.…”
Section: Introductionmentioning
confidence: 99%